Effect of tube shape variations on the mechanical performance of a runflat installation and removal tool using finite element analysis - Dhio Marchel Pratama Putra; Iis Siti Aisyah; Muhammad Hasbi Rusmana; Daryono (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2025)
The increasing demand for operational efficiency in military vehicle maintenance has highlighted the need for effective tools for the installation and removal of runflat systems in armored vehicles. This study investigates the influence of tube cross-sectional geometry on the mechanical performance of a runflat installation and removal tool through finite element analysis (FEA) using ANSYS Workbench 2021 R2. Three tube geometries—hexagonal, octagonal, and circular—were modeled using SS400 structural steel as the material. Two loading scenarios were analyzed: bead loosening and runflat pressing. The evaluated parameters included Von Mises stress, total strain, total displacement, and safety factor. Simulation results indicate that the octagonal tube geometry demonstrated the best overall performance in the bead loosening scenario, with the lowest Von Mises stress (86.078 MPa), minimal strain (0.0001888 mm/mm), moderate displacement (0.62883 mm), and the highest safety factor (2.672). The circular tube geometry achieved the lowest displacement (0.59168 mm) but exhibited higher stress levels. In the runflat pressing scenario, all geometries operated within safe limits, with stress levels ranging from 11–14 MPa and safety factors reaching the maximum value of 15. These findings suggest that an octagonal tube geometry offers an optimal balance between strength, deformation control, and safety, making it suitable for field applications without revealing sensitive manufacturing details.